Thomas Wetmore, The Charter and Ordinances of the City of Boston 116-117 (1834) - (:unkn) unknown (My University, 1826)
An ordinance forbidding the firing of Guns, prohibiting Fireworks in certain cases, and to prevent damage by fire, § 1: That no person shall fire or discharge any gun, fowling piece, or fire arms within the limits of the city, which shall be loaded with balls or shot, or with powder only, under a penalty for every such offence, of a sum not less than one dollar nor more than twenty dollars: Provided, however, that the provisions of this section shall not extend to the firing of any gun or other fire arm, in the lawful defense of the person, family, or property of any citizen; nor to the firing of any such gun or fire arm at any military exercise or reviews.
Keywords: DISCHARGE